Klinično vodenje transfuzije - sodobni pristopi za optimizacijo transfuzije - Poženel, Primož (Zdravniški vestnik, 2015)
As a precious biological substance, donated blood has to be used in a sustainable, safe and efficient manner. Therefore good transfusion practice in modern surgery, anaesthesiology and intensive care is of key importance. New therapeutic methods, operations, transplantation of organs and hematopoietic stem cells often require intensive and long term supportive therapy including transfusions of blood components. Nowadays, transfusion service is confronted with continuously increasing demand for sufficient quantity of safe high quality blood, and on the other hand with limited resources of blood. The article deals with the current modern approaches for optimization of transfusion practice and Patient Blood Management that have to be implemented in Slovenian hospitals.
Keywords: artificial blood replacements; improved transfusion procedures; izboljšani transfuzijski postopki; restrictive blood use; restriktivna uporaba krvi; umetni nadomestki krvi